FAKTOR-FAKTOR YANG MEMPENGARUHI RENDAHNYA CAKUPAN Hb.0 DI DESA SAIT BUHIT PUSKESMAS PEMATANG SIDAMANIK KABUPATEN SIMALUNGUN TAHUN 2019 - sri leni betty saragih (Fakultas Kesehatan Masyarakat, Institut Kesehatan Deli Husada Deli Tua, 2020)
ABSTRACT Immunization is the process by which a person is made immune or resistant to infectious diseases, usually by being given a vaccine. Immunization is important for babies. The antibodies possessed by infants are not perfect, therefore babies need vaccines in the form of immunizations to ward off various diseases that can strike at any time. The mother is a person who plays an important role in caring for children and in making decisions in the household for the completion of child immunization. Hepatitis B vaccine must be given immediately after birth, bearing in mind that hepatitis B vaccination is a very effective preventive measure to break the chain of transmission from mother to her baby immediately after birth. The success of immunization requires community involvement, especially the role of mothers / parents who have babies in immunization. This study aims to determine how the analysis of factors that influence the low HB 0 immunization coverage in the village of Sait Buttu, the working area of Pematang Sidamanik Community Health Center, Simalungun Regency in 2019. This study is a survey with a cross-sectional research design. Sampling is done by purposive sampling technique. The total sample in this study were 76 respondents. Data were analyzed by Chi Square test with α 0.05. The results of the study with bivariate analysis showed that there were influences between factors related to mother's attitudes, namely knowledge with p value (0.030) <α 0.05, education with p value (0.006) <α 0.05, age with p value (0.002 )<α 0.05, and work with a p value (0.004) <α 0.05 in the coverage of HB 0 in the Pematang Sidamanik Community health center in 2019. For the Simalungun District Health Office to provide more information about the benefits of HB-0 immunization, especially to pregnant mothers so that the mother gives HB-0 immunization to her baby later when the baby is born. For the Pematang Sidamanik Community Health Centre so that all midwives in the Community can always provide information to mothers and families to be willing to allow their babies to be given HB-0 immunization immediately after birth (age 0-7 days) Keywords: Mother's Attitude, Low HB 0, and Community Health Centra.